Exercices sur le calcul algébrique

1
(2a - 3b + c).3a =
Solution
2
(-2a).(-a - b + c) =
Solution
3
3ab.(a² - b² + 2ab) =
Solution
4
(6ax²y + 2a²x - 5xy²).(-2xy) =
Solution
5
3a.(a² - 1) - 3a². (a + 1) - 3a =
Solution
6
a².(a + b) - 2b.(a² - 1) + 2 .(a² + 1) =
Solution
7
3xy.(x - y) + 2x.(2xy - 1)- y.(2x² + 1) =
Solution
8
2x.(x² - xy + y²)- 2y.(x² - y²) =
Solution
9
2a² - 3b² + (a - b).(a - 2b) - (2a - b).(a + b) =
Solution
10
(x + 1).(x - 2).(x + 3) - (x - 1).(x + 2).(x - 3) =
Solution

Retour